Long-term effects of ambient particulate matter on hypertension among royal Thai army officers: a retrospective cohort study: 10.55131/jphd/2024/220106 - Poobunjirdkul, Sarun; Laorattapong, Apisorn; Rattananupong, Thanapoom; Jiamjarasrangsi, Wiroj (Journal of Public Health and Development, 2024)
Recent research on the link between exposure to ambient particulate matter with an aerodynamic diameter up to 2.5 microns (PM2.5) and hypertension risk has primarily concentrated on spatial variation (or between-individual comparisons). Research into temporal variations (or within-individual comparisons over time) has largely been neglected. This study sought to examine the spatial–temporal effects of long-term exposure to PM2.5 on hypertension risk among military personnel in Thailand. A retrospective cohort study was conducted, encompassing 40,984 Royal Thai Army officers from 400 army units stationed across 51 provinces in Thailand. Medical check-up data from 2018 to 2021 were analyzed alongside ambient PM2.5 data from 2015 to 2017, sourced from the Geo-Informatics and Space Technology Development Agency. Two parameters, PM2.5-baseline and PM2.5-change, were introduced to assess the impact of spatial and temporal PM2.5 variations on hypertension incidence. Cox proportional hazard regression was used, with hazard ratios (HR) with 95% confidence intervals (95% CI) serving as the measure of association. The association between PM2.5-baseline and hypertension incidence yielded hazard ratios in Quartiles 2 to 4 compared to Quartile 1 of: Q2 HR: 1.19, 95% CI: 1.10–1.28; Q3 HR: 1.10, 95% CI: 1.02–1.20; Q4 HR: 1.13, 95% CI: 1.05–1.22. Additionally, the PM2.5-change showed a J-shaped association with hypertension incidence. Our findings underscore the role of both temporal and spatial factors in hypertension development and highlight the necessity for comprehensive investigations into the causal relationship between PM2.5 exposure and hypertension risk. They also provide valuable insights for devising effective strategies to mitigate the adverse health impacts of PM2.5 pollution.